Negative Emotional Stimuli Enhance Conflict Resolution Without Altering Arousal - Fehring, Daniel J.; Samandra, Ranshikha; Rosa, Marcello G.; Mansouri, Farshad A. (Frontiers in Human Neuroscience, 2019)
In our daily life, we frequently need to make decisions between competing behavioral options while we are exposed to various contextual factors containing emotional/social information. We examined how changes in emotional/arousal state influence resolving conflict between behavioural rules. Visual stimuli with emotional content (positive, negative and neutral) and music, which could potentially alter emotional/arousal states, were included in the task context while participants performed the Wisconsin Card Sorting Test (WCST). The WCST requires the application of abstract matching rules, to resolve conflict between competing behavioural options. We found that conflict influenced both accuracy and response time in implementing rules. Measuring event-related autonomic responses indicated that these behavioural effects were accompanied by concomitant alterations in arousal levels. Performance in the WCST was modulated by the emotional content of visual stimuli and appeared as a faster response and higher accuracy when trials commenced with negative emotional stimuli. These effects were dependent on the level of conflict but were not accompanied by changes in arousal levels. Here, we report that conflict-induced behavioural alterations are accompanied by concomitant changes in participants’ arousal/emotional state. Visual stimuli with emotional content influence conflict resolution and conflict-induced behavioural adjustments without trial-by-trial changes in arousal level. Our findings indicate intricate interactions between emotional context and various aspects of executive control such as conflict resolution and suggest that these interactions are not necessarily mediated through alterations in arousal level.